“I’m with her” or “we’re with her”? Personal versus group leader-based identities and types of political participation - Carty, Emily B. (Revista Latinoamericana de Opinión Pública, 2020)
In a region where personalistic politics and charismatic leaders have long been a characteristic of the political landscape, there has been little research exploring the relationship between individuals’ identification with leaders and its relationship with political participation. Using original survey data from Argentina in 2016, the findings from this study demonstrate a few key points. Firstly, that identities form around political leaders and that identification plays an important role in political participation. Secondly, while personal identification with a leader is related with atomized and collective participation, the relationship between collective identification that is shared with other supporters of the political leader and both types of participation is even stronger. Additionally, these identification measures are more strongly associated with political action in support of a leader than frequently used variables such as partisan identification and ideology. This suggests that the study of political participation, especially in those contexts with more personalized political systems such as are often found in Latin America, should not ignore the role of personal and especially group leader-based identity.